Anglican Cathedrals in Modern Life
XIV, 267 p.
Keywords: In the past decade, cathedrals have blossomed as signs of growth for the Anglican Church in England and Wales. They have opened their doors to growing congregations, to widening participation at the major Christian festivals, and to visitors, pilgrims, and tourists on a changing quest for religious experience and for spiritual fulfilment. In this thought-provoking volume Leslie J. Francis' research group presents ten focused empirical studies that illuminate what is really going on in these cathedrals.